Automated Proofs for Some Stirling Number Identities - Kauers, Manuel; Schneider, Carsten (The Electronic Journal of Combinatorics, 2008)
We present computer-generated proofs for some summation identities for (q-)Stirling and (q-)Eulerian numbers that were obtained by combining a recent summation algorithm for Stirling number identities with a recurrence solver for difference fields.